Cost-effective product prioritisation technique for software product line testing. (28th May 2021) - Kumar, Satendra; Mittal, Mohit; Yadav, Vinod Kumar
Software product line testing (SPLT) is a tedious task due to the generation of large number of products. Products testing sequence plays a significant role so that the testing resources could not be exhausted until all the products are tested. This problem can be overcome using the test case prioritisation (TCP) techniques. Many TCP techniques have been proposed to test SPL products in order, but they have not focused on product cost. The product with the highest cost should be tested first, because testing resources should not be exhausted to reach the main product with higher cost. In this paper, a cost-effective product prioritisation technique for SPLT is proposed in which products are prioritised on the basis of products cost. The rigorous evaluation results show that cost-effective prioritisation order is better than random order and similarity-based order.